Social entrepreneurship - Wasieleski, David M.; Weber, James (Business ethics professor) (Emerald Publishing Limited, 2021)
The Business and Society (BAS) 360 book series is an annual publication targeting cutting-edge developments in the broad business and society field, such as stakeholder management, corporate social responsibility and citizenship, business ethics, sustainability, social entrepreneurship and others. Each volume will feature a comprehensive discussion and review of the current "state" of the research and theoretical developments in a specific business and society area. Volume Five focuses on research drawn from work grounded in Social Entrepreneurship. Leading scholars in this discipline contribute to a 360-degree evaluation of theory, including cross-discipline research, empirical explorations, cross-cultural studies, literature critiques, and meta-analysis projects. Social Entrepreneurship will be useful for emerging and senior business school educators researching and teaching in the business and society field, as well as doctoral and masters level students across the business, social sciences and natural sciences seeking to learn about this multi-discipline and sustained field of management study.
Includes index.
Keywords: Social entrepreneurship.; Business & Economics -- Entrepreneurship.; Entrepreneurship.; elektronické knihy; electronic books